(untitled) (Homoeopathy for All, 2021)
Sinusitis, also known as rhinosinusitis, is inflammation of the mucous membranes that line the para nasal sinuses. It is one of the very common chronic illnesses with a substantial health care impact. As per reports, approximately 20% of patients visit to specialists in allergy and immunology (AI) are related to sinusitisbut unfortunately it is very difficult to treat by conventional treatment.1 Allergic fungal sinusitis (AFS) is relatively new term. Its clinical features, radiological and histopathological findings are not fully understood. In this condition, antibiotics and conventional topical nasal preparations are not much useful. Conventional therapy largely depends on surgical intervention and corticosteroids with adverse effects.2 On the other side, homoeopathy, known for its role in allergic conditions and fungal infections, can help in AFS without surgical invasion. In this article, AFS and its homoeopathic approach are discussed.